INSTAGRAM AS A MEDIA FOR TALKING TO THE @TEMANGAGAL_MUU COMMUNITY ON SOCIAL MEDIA - Wilda Hasanah; Risqi Inayah Dwijayanti; Zhafira Athifah Sandi (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2026)
Instagram as a storytelling media in the @temangagal_muu community, Instagram becomes a story-sharing information tool categorized as social media that can provide a st ory zone in self-disclosure for individuals who do not have social support around them. The @temangagal_muu online community is present as a means of commun ication and a means of educating related to mental health issues. The theoretical foundation used is the communication privacy management theory which explains that every individual has the right to their personal information, so information according to this theory is a variety of types of information that will make individuals control the information they have and use the conceptual basis of communication, social media, Instagram, storytelling, community. The method used is a qualitative approach with a case study technique, constructivism paradigm, descriptive, research nature. Using data collection techniques in the form of online interviews, observation, and documentation. The results of this study indicate that Instagram as a medium of interaction for introverted individuals and as a means of self-disclosure that has a confidential range so that individuals feel safe and comfortable. The completion of Instagram as one of the media used by @temangagal_muu in interacting with individuals, in the activity of managing the publication and interaction activities of the @temangagal_muu online community.